Low-hardness amorphous alloy strip, iron core and manufacturing method of low-hardness amorphous alloy strip

By optimizing the composition and manufacturing process of amorphous alloy strips and reducing their hardness, the problems of uneven finished products caused by high hardness during the stamping and forming process of traditional amorphous alloy strips are solved, and more efficient stamping and forming and lower manufacturing costs.

CN119464968APending Publication Date: 2025-02-18QINGDAO YUNLU ADVANCED MATERIALS TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411671066.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

During the stamping process, traditional amorphous alloy strips have high hardness, resulting in uneven punching pressure, resulting in uneven surface of the finished product, low yield, and large energy consumption, which affects the industrialization of amorphous motors.

Method used

By optimizing the chemical composition and manufacturing process of amorphous alloy strips, the hardness is reduced. The specific component expression is FeaNibPxMyRz. The tape is prepared by combining rapid solidification technology. The planar microhardness HVp0.05≤850, and the cross-sectional microhardness HVs0.05 ≤800.

Benefits of technology

It significantly reduces the hardness of the amorphous alloy strip, improves the yield and efficiency of stamping forming, solves the problem of difficult stamping, and reduces the manufacturing cost of amorphous motors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464968A_ABST
    Figure CN119464968A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of soft magnetic materials, in particular to a low-hardness amorphous alloy strip, an iron core and a manufacturing method of the low-hardness amorphous alloy strip. The chemical component expression is FeaNibPxMyRz, M is one or more of Si, B and C elements, and R is Cu or Au; the atomic percentage contents meet the following conditions: 70 < = a < = 86.5, 0 < = b < = 15, 0 < = x < = 5.5, 0 < = y < = 16, 0 < = z < = 1.5, and a + b + x + y + z = 100; 83.5 < = a + b < = 86.5. By optimizing the components and the manufacturing process of the amorphous alloy strip, the hardness of the amorphous alloy strip is remarkably reduced while the ferromagnetic property of the amorphous alloy strip is ensured, so that the yield of punch forming is improved, and the problem that the amorphous alloy strip is difficult to punch is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of soft magnetic materials, and in particular to a low-hardness amorphous alloy strip, an iron core and a manufacturing method thereof, which are used for manufacturing magnetic components such as motors. Background Art

[0002] Motors are electrical devices with the highest power consumption. Improving motor efficiency plays an important role in energy conservation and emission reduction. Traditional motors generally use silicon steel as the core material, but as the market's requirements for power density and speed characteristics become increasingly higher, silicon steel has been difficult to meet market demand. Amorphous alloy strips have excellent electromagnetic properties such as high magnetic permeability and high resistivity, which can effectively reduce eddy current losses. Therefore, amorphous alloy strips are suitable as core materials in high-frequency motors.

[0003] General Motors of the United States began to study the processing methods of amorphous alloy motor cores in 1978, and manufactured a 250W asynchronous motor using amorphous alloy strips in 1982. With the development of amorphous alloy core processing technology, more and more scholars have applied amorphous strips to various motors.

[0004] Patent WO99 / 66624 discloses an amorphous metal stator for a high-efficiency radial flux motor, which is formed by stacking strips of different lengths into an arc or C shape, and then varnishing and curing to form a stator with teeth in the inner diameter direction. The stator structure formed by this method contains a large number of air gaps between discrete amorphous metal sheets, thereby increasing the magnetic resistance of the magnetic circuit and the corresponding current required to run the motor. Hitachi's patent US6737951B1 discloses a method for processing an amorphous stator core, which stacks amorphous strips, cuts them into polyhedral amorphous blocks with arched surfaces on one or two sides, and then rearranges these amorphous blocks to form a complete stator core. The core components made by this method have advantages in efficiency compared to silicon steel components of the same specifications, but there are air gaps at the joints of each two polyhedral amorphous blocks, which affects the performance of the core to a certain extent.

[0005] Patent US2004 / 001211 of Metglass Corporation of the United States discloses a method of preparing an amorphous iron core stator by cutting laminations by photolithography and etching. This method has complex process, low production efficiency and high cost, and is only suitable for making small-sized amorphous alloy iron cores with complex shapes, but not suitable for mass production of large-sized amorphous alloy iron cores.

[0006] Patent CN101286676A of Antai Technology Co., Ltd. discloses a method for preparing a radial amorphous alloy stator core. The method first stacks amorphous alloy sheets of the same length into an amorphous alloy sheet stack with a predetermined thickness, anneals the sheet stack, performs a paint-immersion curing treatment, and finally cuts it into a stator core. The performance of the amorphous core prepared by this method is significantly improved compared to that of silicon steel core, laying a certain technical foundation for the mass production of amorphous motors.

[0007] In the above patent technologies, it can be found that the current research focus on amorphous motors is on the structure and preparation methods of amorphous motors. The above research is based on the existing conventional iron-based amorphous strips for amorphous motor research. The manufacturing method of amorphous motors is mainly stacked cutting, but this method is very inefficient and not conducive to industrialization. In order to improve the production efficiency of amorphous motors, the processing technology of amorphous strips has been optimized and upgraded in recent years, mainly including stamping methods. However, traditional amorphous alloy strips are high-strength and high-hardness materials, which have high requirements for existing stamping. During the stamping process, due to a certain verticality error of the punch head, the stamping pressure on the surface of the amorphous alloy workpiece is uneven, so that the surface flatness of the finished product is erroneous, resulting in many unqualified products, low stamping stability, waste of resources, and increased costs; uneven stamping pressure will also lead to more stamping times to balance the stamping pressure on the surface of the amorphous alloy, which consumes a lot of energy. To solve the stamping problem of amorphous strips, improvements can be made in two main aspects. On the one hand, the stamping problem can be solved by improving the material of the punch head and the stamping process; on the other hand, the characteristics of amorphous strips are hard and brittle, and the hardness is high, which makes it difficult to process. This problem can be solved by improving the stamping characteristics of amorphous strips. However, while improving the stamping characteristics of amorphous strips, it is also necessary to ensure its ferromagnetic properties such as high saturation magnetic induction intensity and low loss.

[0008] Therefore, it is necessary to provide an improved low-hardness amorphous alloy strip, iron core and a manufacturing method thereof to solve the above problems. Summary of the invention

[0009] The purpose of the present invention is to provide a low-hardness amorphous alloy strip, an iron core and a method for manufacturing the same. From the perspective of composition design, the composition and manufacturing process of the amorphous alloy strip are optimized, while ensuring its ferromagnetic properties, its hardness is significantly reduced, thereby improving the yield of stamping and solving the problem of the difficulty of stamping amorphous strips.

[0010] To achieve the above object, the present invention provides a low-hardness amorphous alloy strip in the first aspect, the chemical composition of which is expressed as: Fe a Ni b P x M y Rz , wherein M is one or more of Si, B and C elements, R is Cu or Au; a, b, x, y, z respectively represent the atomic percentage content of the corresponding elements, satisfying: 70≤a≤86.5, 0≤b≤15, 0≤x≤5.5, 0≤y≤16, 0≤z≤1.5, a+b+x+y+z=100; 83.5≤a+b≤86.5.

[0011] Furthermore, 85.5≤a+b≤86.5; 0.2≤x≤5.5, 5<y≤16, preferably, 8<y≤16.

[0012] Further, M is at least two of Si, B and C elements. Preferably, M includes at least Si and B.

[0013] Furthermore, the atomic content ratio of Si and B is (0.05~0.4):1.

[0014] Furthermore, the chemical composition expression of the low hardness amorphous alloy strip is Fe a P x M y R z , 85.5≤a≤86.5, 1≤x≤5.5, 8<y≤15, a+x+y+z=100, M includes at least Si and B; Alternatively, the chemical composition expression of the low hardness amorphous alloy strip is Fe a Ni b P x M y R z , 80≤a≤86.5, 0≤b≤10, 1<x≤5.5, 8<y≤16, 0≤z≤1.5, a+b+x+y+z=100; 85.5≤a+b≤86.5.

[0015] Furthermore, the method for preparing the low-hardness amorphous alloy strip includes: pouring molten steel onto the surface of a rotating cooling roller through a nozzle, wherein the pouring temperature is ≥1470°C; controlling the distance between the nozzle and the cooling roller to be 0.3-0.5mm, and the roller speed of the cooling roller to be 25-35m / s.

[0016] Further, according to Fe a Ni b P x M y R z The alloy components are mixed and the raw materials are remelted; after the smelting is completed, the temperature is raised and kept to calm the steel, and then the molten steel is poured onto the surface of the rotating cooling roller through a nozzle; the pouring temperature is 1470°C to 1480°C.

[0017] Furthermore, the low-hardness amorphous alloy strip has a thickness of 26±2 μm and a width of 20-80 mm.

[0018] Furthermore, the plane microhardness of the low-hardness amorphous alloy strip is HV p 0.05≤850; Cross-section microhardness HV s 0.05≤800; Crystallization temperature Tx≤450℃.

[0019] The second aspect of the present invention provides an iron core, which is prepared by stamping the low-hardness amorphous alloy strip described in any one of the above items. The low-hardness amorphous alloy strip provided by the present invention is particularly suitable for stamping the iron core. Due to its moderate hardness and good formability, it has high stamping flatness and good stability, which can significantly improve the stamping efficiency.

[0020] A third aspect of the present invention provides an amorphous motor, comprising the iron core described above.

[0021] The beneficial effects of the present invention are as follows: 1) The low-hardness amorphous alloy strip provided by the present invention optimizes the composition and manufacturing process of the amorphous alloy strip, significantly reduces its hardness while ensuring its ferromagnetic properties, thereby improving the yield of stamping and solving the problem of difficulty in stamping amorphous strips.

[0022] 2) The use of the amorphous alloy strip with low hardness provided by the present invention can effectively improve the stamping efficiency and facilitate the large-scale manufacturing of amorphous motors. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 This is a physical picture of the plane hardness sample.

[0025] Figure 2 This is a physical picture of the cross-section hardness sample.

[0026] Figure 3 These are the indentation diagrams of hardness test: (a) plane hardness indentation diagram, (b) cross-section hardness indentation diagram.

[0027] Figure 4 This is the relationship between microhardness and crystallization temperature. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Compared with silicon steel, amorphous alloy strips have higher resistivity and thinner strip thickness, so when used as core materials, iron loss can be reduced by 70% to 90%. Within the operating frequency range of the motor, the loss of iron-based amorphous alloys can be reduced to 1 / 3 of silicon steel, so using amorphous alloys as motor cores can significantly improve motor efficiency. In the process of manufacturing amorphous motors, the processing of amorphous strips is the most core process in the manufacturing process. At present, the processing of amorphous strips mostly adopts the method of solidification cutting, but this method is complicated, inefficient, and costly. Compared with silicon steel motors, the cost will increase too much. In order to improve the processing efficiency of amorphous motors, stamping is used for processing, but the high strength and hardness of amorphous strips bring more difficulties to the stamping process.

[0030] During the research on stamping technology, it was found that the hardness of the material is inversely proportional to the wear constant of the stamping die. The greater the wear constant of the stamping die, the more stamping times, the greater the stamping efficiency, and the lower the cost. From this perspective, without considering improving the stamping equipment and stamping die, reducing the hardness of the stamping material is the most effective method. As a stamping material for amorphous motors, a lower hardness value of amorphous strip can effectively improve stamping efficiency and reduce the cost of amorphous motors.

[0031] Amorphous strips used in the traditional power electronics industry generally have greater hardness. Due to the short-range orderly arrangement of atoms in amorphous alloys, the bonds between atoms are stronger than those in general crystalline alloys, and there are no defects such as dislocations, so there will be no movement and slip of dislocations. Therefore, amorphous alloys have higher strength, hardness and excellent soft magnetic properties. For example, the commonly used Fe 78 SiC 13 The HV 0.05 of the alloy is about 920. Therefore, it is necessary to optimize its composition and manufacturing process to obtain a low-hardness amorphous alloy strip.

[0032] The low-hardness amorphous alloy strip provided by the present invention has a chemical composition expression of: Fe a Ni b P x M y R z, wherein M is one or more of Si, B and C elements, R is Cu or Au; a, b, x, y, z respectively represent the atomic percentage content of the corresponding elements, satisfying: 70≤a≤86.5, 0≤b≤15, 0≤x≤5.5, 0≤y≤16, 0≤z≤1.5, a+b+x+y+z=100; 83.5≤a+b≤86.5; prepared by rapid solidification technology.

[0033] The amorphous alloy strip has the following characteristic parameters: plane microhardness HV p 0.05≤850, preferably HV p 0.05≤830; Cross-section microhardness HV s 0.05≤800, preferably HV s 0.05≤740.

[0034] At present, the microhardness of the amorphous material of the present invention is more than 7% lower than that of the conventional amorphous strip. After the stamping experiment, the amorphous strip conforming to the present invention can effectively increase the number of stamping times.

[0035] Specifically, the amorphous alloy strip is mainly composed of ferromagnetic elements and metalloid elements. Among them, Fe and Ni are ferromagnetic elements, which are the main sources of magnetism of amorphous strips. The Fe content is an important guarantee for the strip to have a suitable saturation magnetic flux density value, and too high Fe content will cause the alloy's amorphous forming ability to decrease, making industrial production difficult to achieve. The present invention uses 70at%~86.5at% Fe content, preferably 80at%~86.5at%, which can ensure that the saturation magnetic flux density of the strip is above 1.56T, meeting the use requirements of amorphous motors. The present invention optimizes the types and contents of components, and can not affect the amorphous forming ability even when the Fe content is high.

[0036] In the present invention, the main function of adding Ni element is to reduce the hardness. When Ni element is added to an amorphous alloy mainly composed of Fe element, the average outer electron concentration (e / a) of metal atoms can be increased. The larger this parameter is, the lower the hardness is. In the present invention, the range of Ni element is: 0<b≤15. When the atomic content of Ni element exceeds 15at%, the saturation magnetic induction intensity of the alloy system will drop below 1.56T, which cannot meet the design requirements of amorphous motors.

[0037] In the present invention, in order to ensure the low hardness and manufacturability of the alloy, the total amount of ferromagnetic elements needs to be controlled within 83.5≤a+b≤86.5, preferably 85.5≤a+b≤86.5. When the total amount of iron and nickel elements is ≤83.5at%, the hardness of the amorphous strip cannot meet the requirements, and when the total amount of iron and nickel elements is ≥86.5at%, the amorphous forming ability of the alloy decreases, making industrial production difficult to achieve.

[0038] P, Si, B, and C are amorphous forming elements, which are necessary conditions for the alloy system to form amorphous under industrial production conditions. In early literature, the hardness of the Fe-P binary alloy is the lowest among all Fe-M alloy systems. Based on this, in order to achieve the requirements of both low hardness and mass production, the present invention optimizes the composition on the basis of the Fe-P binary system. The range of the P element: 0<x≤5.5, preferably 0.2≤x≤5.5. In the metalloids of this system, P is an essential element and the basic guarantee of low hardness, but the atomic content of the P element ≥5.5% will reduce the preparability of the alloy system. In the actual production process, the source of the P element is mainly ferrophosphorus. The quality of ferrophosphorus is relatively high compared to other metal raw materials, and there are too many impurity elements in it. During the smelting process, the quality of the molten steel will decrease, and the difficulty of preparing the strip will increase; on the other hand, the P element is relatively poor in stability and easy to oxidize compared to other metalloid elements. The strip containing a high content of the P element is prone to oxidation phenomena such as bluing during heat treatment. Therefore, it is necessary to control the content ≤5.5at% Other metalloid elements can be selected from Si, B, and C. These elements are all amorphous forming elements. The addition of Si can increase the degree of disorder of the alloy system, lower the melting point of the alloy, improve the fluidity of molten steel, and reduce the difficulty of preparation. Too high Si content will cause the alloy composition to deviate from the eutectic point and reduce the amorphous forming ability. Element B is the most important amorphous forming element. Element C is also an amorphous forming element. On the one hand, using element C instead of element B can further enhance the amorphous forming ability of the alloy system; on the other hand, element C itself can improve the wettability of the melt and the cooling roller and improve the preparation process. However, the mixing enthalpy of C atoms and Fe atoms is positive, and excessive addition will cause the amorphous forming ability to deteriorate, so the content of element C needs to be controlled. From the perspective of low hardness, it has been found through research that the effect of metalloids is Si>C>B. In the present invention, 0.0<y≤16, preferably 5<y≤16.

[0039] R is Cu or Au element. Adding Cu or Au element to the alloy system can effectively reduce the crystallization temperature of the alloy system. According to literature reports, the crystallization temperature is inversely proportional to the hardness. The lower the crystallization temperature, the lower the hardness of the alloy system. In the present invention, the atomic ratio content of the R element is: 0≤z≤1.5. If the Cu and Au contents are too high, the amorphous forming ability of the alloy will be reduced. Primary crystallization occurs during the tape making process, which increases the hardness. The present invention determines that the atomic percentage content of the R element is 0-1.5% through a large number of experiments. In the present invention, R is preferably the Cu element.

[0040] The amorphous alloy strip of the present invention has a relatively low crystallization temperature Tx, wherein Tx≤450°C. During the research period at the beginning of the research of the present invention, it was reported in the literature that for bulk amorphous alloys, its elastic modulus E is proportional to the crystallization temperature Tx, and the elastic modulus E=20Hv, that is, the crystallization temperature is proportional to the hardness. During the research period, the present invention took this as the starting point for design, and found that this theory is also applicable to amorphous alloy strips, and the crystallization temperature of the strips that meet the hardness requirements of the present invention is ≤450°C.

[0041] A second aspect of the present invention provides a method for manufacturing an amorphous alloy strip, wherein the amorphous strip is prepared by a rapid solidification process, and during the preparation process, the amorphous strip is obtained by adjusting the following process parameters: (1) pouring the molten steel onto the surface of a rotating cooling roll through a nozzle, wherein the pouring temperature is at least 1470°C.

[0042] (2) During the strip making process, the distance between the nozzle and the cooling roller is controlled at 0.5-0.3 mm, and the roller speed of the cooling roller is controlled at 25-35 m / s.

[0043] During the preparation experiment, it was found that the experimental compositions that meet the requirements of the present invention all have a relatively high liquidus temperature. In order to make the molten steel have a certain fluidity and smooth pouring, the pouring temperature is at least 1470°C. If the pouring temperature is lower than 1470°C, strip burrs, slag lines and even nozzle blockage will occur. Due to the high pouring temperature of the alloy, in order to obtain a completely amorphous strip, a high requirement is placed on the cooling capacity of the pouring process. In order to achieve high cooling capacity, during the preparation process, the process idea adopted is high roller mouth spacing and high roller speed.

[0044] The present invention further provides an amorphous motor, the core material of the amorphous motor is prepared by stamping the amorphous strip material of the present invention, and the amorphous motor of the present invention has a higher stamping efficiency than the traditional amorphous motor. Specific embodiments The present invention is based on Fe a Ni b P x M y R z The alloy composition is prepared, and the raw materials such as iron source, nickel plate, metallic silicon, ferroboron, ferrophosphorus, electrolytic copper, etc. with different proportions are remelted in a medium frequency smelting furnace. After smelting, the steel is discharged to a medium frequency bottom building furnace. After heating and keeping calm, a single-roller rapid quenching method is used to prepare an amorphous alloy strip with a width of 60 mm and a thickness of 26±2 μm.

[0046] Strip evaluation: For the alloy strip of the present invention, the following aspects need to be evaluated: ① Structural analysis: Use an X-ray diffractometer to determine whether the prepared strip is completely amorphous; ②Thermodynamic performance analysis: Use a synchronous thermal analyzer to test the crystallization temperature of the prepared strip; ③ Microhardness evaluation: The hardness evaluation of the amorphous strip of the present invention is mainly divided into two dimensions: plane hardness and cross-sectional hardness. p Refers to the hardness of the amorphous strip in the length or width direction, and the cross-sectional hardness HV s It refers to the hardness of the amorphous strip in the thickness direction. The equipment used for hardness testing is a microhardness tester. During the stamping process, the contact between the punch and the strip can be divided into two processes. The first is the contact between the punch and the plane of the strip. In this process, the plane hardness has a greater impact. The second process is the breaking process. In this process, the punch contacts the cross section of the strip, which has a greater impact on the cross section hardness of the strip. Therefore, in the present invention, the evaluation of the strip hardness is divided into two aspects.

[0047] First is the plane hardness: during the test, cut a 1cm*1cm amorphous strip and use adhesive to stick the amorphous strip on the test sample table. The surface of the strip must be flat and clean, and then the test is carried out. The test force is F: 0.4904N. Figure 1 Placement diagram for the sample.

[0048] The second is the cross-sectional hardness: For cross-sectional hardness, the first step is to cut a 1cm*1cm amorphous strip and use the inlay method to prepare the sample. In order to ensure the observability of the sample and the test accuracy of the prepared sample, the cold inlay method is required to prepare the sample. During the experiment, overheated inlay was also used for sample preparation, but the sample would be squeezed and deformed during the preparation process. After grinding and polishing, the sample could not remain vertical, and the measurement results fluctuated greatly. The cold inlay method can avoid the use of metallographic sample clamps to vertically inlay the strip. It will neither float nor deform under force, and a straight sample can be obtained. The hardness value of the test fluctuates less, and the indentation is clear and symmetrical. After the test sample is prepared, a microhardness tester is used for testing, and the test force is selected as F: 0.4904N. Figure 2 This is the cross-sectional hardness sample diagram.

[0049] During the test, at least 5 test points were selected for each sample. The indentation was clear and the symmetry was less than 5%. The average value of the 5 test points was taken as the microhardness value HV0.05 of the sample. Figure 3 These are the plane hardness and cross-section hardness indentation diagrams.

[0050] Table 1 shows the crystallization state, crystallization temperature and microhardness value of the alloy components of the present invention. Examples 1-20 are alloy components in accordance with the present invention, and the rest are comparative examples. Figure 4 The crystallization temperature and plane microhardness HV of the present invention p 0.05, cross-sectional microhardness HV s 0.05 relationship diagram.

[0051] Table 1 Crystallization state, crystallization temperature and microhardness value of alloy components of the present invention

[0052] From the experimental data in Table 1, the following conclusions can be drawn: the amorphous alloys conforming to the present invention can be used to prepare completely amorphous strips, whose plane hardness HVp 0.05 is ≤850, cross-sectional hardness HVs 0.05 is ≤800, and crystallization temperature Tx is ≤450°C. Figure 4 It can also be seen that the lower the crystallization temperature, the lower the hardness of the strip. Comparative Example 1 is a conventional amorphous strip. A completely amorphous strip can be obtained during the preparation process, but its plane hardness is 910.6 and its cross-sectional hardness is 828.9, both of which are higher than those of the present invention. Comparative Example 2 has a higher manufacturing difficulty during the preparation process, and the strip crystallizes. Although its Tx is lower, its hardness is also higher. This is mainly because the strip crystallizes during the preparation process, and the dispersed grains play a strengthening role, resulting in a higher hardness of the strip. Comparative Example 3 keeps phosphorus unchanged and reduces the iron content during the preparation process relative to Example 1, but the plane hardness and cross-sectional hardness are both higher than those of the present invention.

[0053] Table 2 Ferromagnetic properties of examples and comparative examples

[0054] As can be seen from Table 2, Fe and Ni, as ferromagnetic elements, can be counted according to the total ferromagnetic element content, but when the Ni content is too much, the saturation magnetic flux density will be slightly reduced, and when it usually exceeds 5at%, it will be found that it changes significantly. However, each embodiment in the above table can maintain a saturation magnetic flux density greater than 1.63T on the basis of low hardness, indicating that the amorphous alloy strip of the present invention has low hardness while ensuring its ferromagnetic properties, which can improve the yield of stamping and solve the problem of high difficulty in stamping amorphous strips.

[0055] Process Validation In the present invention, Example 4 is selected: Fe 84.8 Ni 0.3 P 2.4 Si 2.5 B 9.8 C 0.2 The alloy composition is used for process verification. According to the above alloy composition, the raw materials such as iron source, nickel plate, metal silicon, ferroboron, and ferrophosphorus are remelted in a medium frequency smelting furnace. After smelting, the steel is tapped into a medium frequency bottom furnace. After heating and keeping calm, a single-roller rapid quenching method is used to prepare an amorphous alloy strip with a width of 30 mm and a thickness of 26±2 μm. Table 3 shows the crystallization state and hardness test values ​​of the strip under different process conditions of Example 4.

[0056] Table 3 Crystallization state and hardness of the strip in Example 4 under different process conditions

[0057] In Table 3, three groups of experiments were conducted, corresponding to the adjustment of the pouring temperature, the adjustment of the roller mouth distance and the adjustment of the roller speed. Among them, S represents the process parameters of the embodiment, and D represents the process parameters of the comparative example. The following conclusions can be drawn from Table 2: 1) From S1 and D1, it can be seen (adjusting the pouring temperature): For Example 4, the pouring temperature is at least 1470°C. Below this temperature, the fluidity of the molten steel will deteriorate, the molten steel will be blocked at the nozzle, and the molten steel will not be able to flow out. The strip obtained from S1 is completely amorphous and has a low hardness.

[0058] 2) It can be seen from S1, S2, S3, D2 and D3 (adjusting the roller mouth spacing): for S1-S3, the roller mouth spacing is controlled at 0.3-0.5mm, and completely amorphous strips can be prepared with low hardness. For D2, the roller mouth spacing is set at 0.6mm, and strips can be formed, but the strip shows crystallization and has a high hardness; for D3, the roller mouth spacing is set at 0.2mm, and the nozzle is blocked, and the strip cannot be prepared. The main reason is that the alloy of the present invention has a high content of ferromagnetic elements and a high liquidus temperature. During the pouring process, as the temperature of the molten steel decreases, the viscosity of the molten steel increases, and a too low roller mouth spacing cannot allow the molten steel to flow out smoothly.

[0059] 3) It can be seen from S1, S4, S5, D4 and D5 (adjusting the cooling roller speed): For S1, S4, S5, the speed of the cooling roller is controlled at 25-35m / s, and completely amorphous strips can be prepared, and the hardness is relatively low. For D4, the speed of the cooling roller is 20m / s, and the strip can be prepared, but slight crystallization occurs, and the hardness is lower than that of traditional amorphous strips, but it cannot meet the requirements of the present invention. For D5, the speed of the cooling roller is 40m / s, and the strip can be prepared, but the strip is severely crystallized and the hardness is high. From the comparative experiment, whether the roller speed is too high or too low, the cooling capacity of the cooling roller will be affected.

[0060] In summary, the use of the low-hardness amorphous strip prepared by the present invention to manufacture amorphous motors can effectively improve the stamping efficiency and thus reduce the manufacturing cost of the amorphous motors.

[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A low-hardness amorphous alloy strip, characterized in that: Its chemical composition expression is: Fe a Ni b P x M y R z , wherein M is one or more of Si, B and C elements, R is Cu or Au; a, b, x, y, z respectively represent the atomic percentage content of the corresponding elements, satisfying: 70≤a≤86.5, 0≤b≤15, 0≤x≤5.5, 0≤y≤16, 0≤z≤1.5, a+b+x+y+z=100; 83.5≤a+b≤86.

5.

2. The low-hardness amorphous alloy strip according to claim 1, characterized in that: 85.5≤a+b≤86.5; And / or, 0.2≤x≤5.5, 5<y≤16, preferably, 8<y≤16.

3. The low-hardness amorphous alloy strip according to claim 1, characterized in that: M is at least two of Si, B and C elements. Preferably, M includes at least Si and B.

4. The low-hardness amorphous alloy strip according to claim 3, characterized in that: The atomic content ratio of Si and B is (0.05~0.4):

1.

5. The low-hardness amorphous alloy strip according to claim 1, characterized in that: The chemical composition expression of the low hardness amorphous alloy strip is Fe a P x M y R z , 85.5≤a≤86.5, 1≤x≤5.5, 8<y≤15, a+x+y+z=100, M includes at least Si and B; Alternatively, the chemical composition expression of the low hardness amorphous alloy strip is Fe a Ni b P x M y R z , 80≤a≤86.5, 0≤b≤10, 1<x≤5.5, 8<y≤16, 0≤z≤1.5, a+b+x+y+z=100; 85.5≤a+b≤86.

5.

6. The low-hardness amorphous alloy strip according to claim 1, characterized in that: The method for preparing the low-hardness amorphous alloy strip comprises: pouring molten steel onto the surface of a rotating cooling roller through a nozzle, wherein the pouring temperature is ≥1470°C; controlling the distance between the nozzle and the cooling roller to be 0.3-0.5mm, and the roller speed of the cooling roller to be 25-35m / s; Preferably, Fe a Ni b P x M y R z The alloy components are mixed and the raw materials are remelted; after the smelting is completed, the temperature is raised and kept to calm the steel, and then the molten steel is poured onto the surface of the rotating cooling roller through a nozzle; the pouring temperature is 1470°C to 1480°C.

7. The low-hardness amorphous alloy strip according to any one of claims 1 to 6, characterized in that: The low-hardness amorphous alloy strip has a thickness of 26±2 μm and a width of 20-80 mm.

8. The low-hardness amorphous alloy strip according to any one of claims 1 to 7, characterized in that: The plane microhardness of the low-hardness amorphous alloy strip is HV p 0.05≤850; Cross-section microhardness HV s 0.05≤800; Crystallization temperature Tx≤450℃.

9. An iron core, characterized in that: The low-hardness amorphous alloy strip according to any one of claims 1 to 8 is prepared by stamping.

10. An amorphous motor, characterized in that: Comprising the iron core as claimed in claim 9.

Citation Information

Patent Citations

  • Preparing method for amorphous alloy stator iron core of high-speed electric machine

    CN101286676A

  • Color image processing apparatus and method

    US20040001211A1

  • Bulk amorphous metal inductive device

    US6737951B1

  • Amorphous metal stator for a radial-FLUX electric motor

    WO1999066624A1